2011
DOI: 10.1128/jvi.02290-10
|View full text |Cite
|
Sign up to set email alerts
|

The Role of LAT in Increased CD8 + T Cell Exhaustion in Trigeminal Ganglia of Mice Latently Infected with Herpes Simplex Virus 1

Abstract: Herpes simplex virus (HSV) infection is a classic example of latent viral infection in humans and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
176
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(231 citation statements)
references
References 82 publications
38
176
0
5
Order By: Relevance
“…was determined by quantitative PCR (qPCR) using primers from the gB region of the HSV-1 genome. Consistent with previous reports (12,49), there was significantly more HSV-1 DNA in TG from WT mice latently infected with LAT(ϩ) virus than in those infected with LAT(Ϫ) virus (Fig. 3A, WT) (P Ͻ 0.0001), which is characteristic of more latency with LAT(ϩ) than LAT(Ϫ) virus in WT mice.…”
Section: Hsv-1 Receptors and Latencysupporting
confidence: 92%
See 2 more Smart Citations
“…was determined by quantitative PCR (qPCR) using primers from the gB region of the HSV-1 genome. Consistent with previous reports (12,49), there was significantly more HSV-1 DNA in TG from WT mice latently infected with LAT(ϩ) virus than in those infected with LAT(Ϫ) virus (Fig. 3A, WT) (P Ͻ 0.0001), which is characteristic of more latency with LAT(ϩ) than LAT(Ϫ) virus in WT mice.…”
Section: Hsv-1 Receptors and Latencysupporting
confidence: 92%
“…We have previously shown that LAT functions as an immune evasion gene (49,65), as an antiapoptosis gene (11), and as an inhibitor of productive infection (45). All three of these LAT functions would seemingly contribute to enhancing HSV-1 latency and the HSV-1 reactivation phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…+ T-cells (Theil et al, 2003a;Verjans et al, 2007) that are primed in the periphery (Held et al, 2012) and LAT functions in part to protect neurons from granzyme B-induced apoptosis (Allen et al, 2011;Jiang et al, 2011). LAT, although dispensable to the establishment of latency, does play an active role in silencing HSV-1 lytic gene promoters during establishment of latency in part by facilitating methylation of lysine 9 on histone H3, a post-translational modification indicative of heterochromatin structures (Wang et al, 2005).…”
Section: During Latency Hsv-1 and Vzv Gene Transcription Is Restrictedmentioning
confidence: 99%
“…Due to a non-canonical splice site junction, the 1.5 kb HSV-1 LAT remains as a stable lariat in the neuronal nucleus with a half-life of 24 h (Spivack et al, 1991;Wu et al, 1996;Thomas et al, 2002;Ng et al, 2004). LAT-containing neurons are occasionally surrounded by CD8 + T-cells (Theil et al, 2003a;Verjans et al, 2007) that are primed in the periphery (Held et al, 2012) and LAT functions in part to protect neurons from granzyme B-induced apoptosis (Allen et al, 2011;Jiang et al, 2011). LAT, although dispensable to the establishment of latency, does play an active role in silencing HSV-1 lytic gene promoters during establishment of latency in part by facilitating methylation of lysine 9 on histone H3, a post-translational modification indicative of heterochromatin structures (Wang et al, 2005).…”
mentioning
confidence: 99%